Does re-amputation following lower extremity amputation in diabetic or dysvascular patients negatively affect survival - EROL, BÜLENT (My University, 2022)
Objective: We aimed to investigate the characteristics of patients who underwent unilateral amputation due to diabetes and peripheral artery disease, as well as the risk factors that cause re-amputation, and to determine these patients’ survival status and the risk factors for mortality. Patients and Methods: This retrospective study included 133 patients who underwent amputation due to diabetes and peripheral arterial disease between 2012 and 2018. The etiology of amputation, the re-operation rate and time to re-operation following initial amputation, survival status and follow up results were accessed from hospital records. Results: Twenty-eight patients underwent amputation due to peripheral arterial disease, whereas 105 patients had peripheral vasculopathy due to diabetes mellitus. The re-operation rate was 33.8%, and the median period from initial surgery to the second surgery was six-weeks. Sixty-six deceased patients survived with a median of 6 months following initial operation. Conclusion: The most crucial factor causing re-amputation was the non-healing wound problems. Patients with amputation should be followed up carefully for wound problems in the six weeks after surgery. Advanced age, American Society of Anesthesiologist grade 4 patients, associating neurological disease, low albumin level, low lymphocyte count and postoperative intensive care unit requirement were all poor prognostic factors for survival. Re-amputation had no negative effect on survival..
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Amputation; Diabetes mellitus; Lower extremity; Reoperation rate; Mortality; Peripheral arterial disease; RISK-FACTORS; FOOT; LEVEL; Amputation; Diabetes mellitus; Lower extremity; Reoperation rate; Mortality; Peripheral arterial disease